Curators, collections, and contexts : anthropology at the Field Museum, 1893-2002 / Fieldiana, Anthropology, new series, no.36 - Nash, Stephen Edward, 1964-; Feinman, Gary M.; Field Museum of Natural History. (Chicago, Ill. : Field Museum of Natural History, 2003)
Includes bibliographical references (p. 319-333). Foreword / John W. McCarter -- Acknowledgments / Stephen E. Nash and Gary M. Feinman -- Introduction: A glorious foundation: 109 years of anthropology at the Field Museum of Natural History / Stephen E. Nash and Gary M. Feinman -- Part 1. A context for Field Museum anthropology -- 1. A natural history of man: reflections on anthropology, museums, and science / Don D. Fowler -- 2. The role of museums in American anthropology / Donald Collier and Harry S. Tschopik, Jr. -- 3. Creating field anthropology: why remembering matters / David R. Wilcox -- 4. "In Re: Founding of the Field Museum" / Edward Everett Ayer -- 5. The Department of Anthropology of the Field Columbian Museum - a review of six years / George A. Dorsey -- 6. A chronicle of Field Museum anthropology / Warren Haskin, Stephen E. Nash, and Sarah Coleman. -- Part 2. A selection of curators -- Interchapter / Stephen E. Nash and Gary M. Feinman -- 7. George Amos Dorsey: a curator and his comrades / Tristan Almazan and Sarah Coleman -- 8. Albert Buell Lewis: realizing George Amos Dorsey's vision / Robert L. Welsch -- 9. Berthold Laufer / Bennet Bronson -- 10. Henry Field, collections, and exhibit development, 1926-1941 / Ed Yastrow and Stephen E. Nash -- 11. A tale of two Thompsons: the contributions of Edward H. Thompson and J. Eric S. Thompson to anthropology at the Field Musem / Donald McVicker -- 12. Wilfrid D. Hambly and Sub-Saharan Africa research at the Field Museum, 1928-1953 / Raymond Codrington -- 13. Paul Sidney Martin / Stephen E. Nash -- 14. Recollections of the Department of Anthropology in the Mid-Twentieth Century / Elaine Bluhm Herold -- 15. Donald Collier: a curator's life / John E. Staller -- 16. My life with exhibits at the Field Museum, 1941-1976 / Donald Collier -- 17. The legacy of James W. VanStone in museum and arctic anthropology / Jessica M. Rooney and Chapurukha M. Kusimba -- Part 3. Present and future challenges -- 18. The changing role of the curator / Jonathan Haas -- 19. Information management in the Department of Anthropology: history and prospects / Dorren Martin-Ross and William K. Barnett -- 20. A foundation for the future of Field Museum anthropology / Stephen E. Nash and Gary M. Feinman -- Part 4. Appendices. Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).